Grammatical Analysis of Verb Types and Their Iʿrāb in Sūrat al-Ṣaff and Sūrat al-Nisāʾ - Moh. Supriyadi; Syahrul Abidin; Asmaa Muhammad Sulaiman Jaad (Dzil Majaz: Journal of Arabic Literature, 2026)
Understanding the types of fi‘il (verbs) and their i‘rab (grammatical inflections) is fundamental to interpreting the meanings of the Qur’an accurately. However, studies that comprehensively examine verb classifications and grammatical inflections in specific Qur’anic chapters remain limited. Therefore, this study aims to identify the types of fi‘il and analyze their i‘rab in Surah As-Shaff and Surah An-Nisa. The research employed a qualitative descriptive approach using the library research method. The primary data source was the Qur’an, particularly Surah As-Shaff and Surah An-Nisa, while secondary sources included books on Arabic grammar (nahwu), morphology (sharaf), and Qur’anic exegesis (tafsir). Data were collected through documentation, intensive reading, and textual analysis of all verses containing verbs. The findings reveal a total of 117 verbs in the two surahs. Surah As-Shaff contains 13 fi‘il māḍī, 18 fi‘il muḍāri‘, and 1 fi‘il amr, whereas Surah An-Nisa contains 15 fi‘il māḍī, 26 fi‘il muḍāri‘, and 24 fi‘il amr. The analysis further demonstrates that variations in i‘rab are closely associated with the syntactic roles and contextual meanings of the verbs, highlighting the precision and richness of Qur’anic linguistic structures. This study contributes to Arabic linguistic scholarship by providing a systematic grammatical analysis of Qur’anic verbs and offering a practical reference for teaching Arabic grammar, Qur’anic studies, and semantic interpretation.